Excellent supercapacitance performance of 3-D mesoporous carbon with large pores from FDU-12 prepared using a microwave method. Issue 31 (9th May 2018) - Cha, Wang Soo; Talapaneni, Siddulu Naidu; Kempaiah, Devaraju M.; Joseph, Stalin; Lakhi, Kripal Singh; Al-Enizi, Abdullah M.; Park, Dae-Hwan; Vinu, Ajayan
Abstract : Highly ordered and three-dimensional (3-D) mesoporous carbon materials were prepared through a nano-hard templating approach using FDU-12 silica with tunable pore sizes as a template, which was synthesized via a microwave-assisted method. Abstract : Highly ordered and three-dimensional (3-D) mesoporous carbon materials were prepared through a nano-hard templating approach using FDU-12 silica with tunable pore sizes as a template, which was synthesized via a microwave-assisted method. Powder XRD and microscopic techniques such as HR-TEM, HR-SEM, and N2 adsorption–desorption techniques were employed to characterize the structure and textural properties of the prepared mesoporous carbon samples. The characterization results reveal that all the mesoporous carbon samples show a 3-D porous mesostructure with tunable pore diameters (5.7 to 9.4 nm) and a large specific surface area in the range from 451 to 1251 m 2 g −1 . The supercapacitive behavior of the cubic structured mesoporous carbons was determined using cyclic voltammetry, electrochemical impedance and charge–discharge measurements. The cubic mesoporous carbon materials exhibit a superior capacitive performance with a high specific capacitance value of 315.3 F g −1 at the current density of 1 A g −1, which is much higher than that of hexagonally-ordered mesoporous carbon with large pore diameters, activated carbon, and carbon nanotubes. The materials also show excellent cyclic stability and extremely low resistance. The superior specific capacitance of these materials is attributed to the combination of excellent surface properties such as large specific surface area, large pore volume and uniform pore diameter, spherical morphology, and a 3-D porous system with cage-type pores.